Clustering In Fingerprint Recognition System. - Ooi, Boon Yaik; Cheng, Wai Khuen; Salam, Rosalina Abdul; Sumari, Putra (2004)
Clustering of fngerprints can help to reduce the complesity of the search process in a database.